Do wild ungulates experience higher stress with humans than with large carnivores?. (16th November 2017) - Zbyryt, Adam; Bubnicki, Jakub W; Kuijper, Dries P J; Dehnhard, Martin; Churski, Marcin; Schmidt, Krzysztof
Abstract : Predation is a major selective pressure for prey; however, whether it evokes stronger stress response relative to anthropogenic factors in wild populations of animals is not clear. We studied the stress levels in red deer and roe deer in 6 populations exposed to potentially different levels of stress. We showed that stress levels in wild ungulate populations are lower and less variable in areas with large carnivores than in carnivore-free areas where human-related factors predominate. Abstract: Predation is a major selective pressure for prey; however, the stress response to predation risk and the relative importance of natural versus anthropogenic stress factors in wild populations of animals have rarely been studied. We investigated the level of fecal glucocorticoid metabolites (FGMs) in 6 populations of red deer and roe deer exposed to potentially different levels of stress, resulting from both natural (predator presence, forest cover, undergrowth, ungulate density, and temperature) and anthropogenic (hunting harvest, percentage of build-up areas, and road density) factors. We found the highest and most variable FGM concentrations in both ungulates in areas without large carnivores, and the lowest and least variable FGM levels in areas with wolf and lynx. Anthropogenic factors (hunting harvest, roads, and built-up area) positively correlated with the gradient of FGM levels in both species. Both the mean and the variance of the FGM concentrations measured within populations of both red deer and roe deer were affected positively by variation in hunting harvest and negatively by the minimum temperature. The variance in the roe deer FGM was also positively influenced by the percentage of built-up areas. The results indicate that stress in wild ungulate populations is lower and less variable in areas utilized by large carnivores than in carnivore-free areas where human-related factors predominate. This may be explained by evolutionary adaptations of prey animals constantly exposed to the risk of natural predation and their inability of adapting to the risk from humans probably due to its high intensity and erratic occurrence.